ANALYSIS OF AFFECTING RICE FARMERS INCOME IN KEDUNGPRING VILLAGE KEC. KEDUNGPRING KAB. LAMONGAN - Ike Susanti; Akhlis Priya Pambudi; Ruswaji Ruswaji; Nur Maziyatul (UNIVERSITAS PAKUAN, 2022)
The existence of social and economic factors that are owned by each farmer certainly results in differences. This can be attributed to the capacity of the farmers in producing rice crops and increasing business income in agriculture. The purpose of the study is to explain the analysis that affects the income of rice farmers. The research method used is quantitative method using analytical test tools in the form of T-test, multiple linear regression analysis, Coefficient of Determination Test, and F-test. The results of the data analysis are known that for X2 t test results obtained tcount (3.286) is greater than ttable (1.984) with df = (n-k), at a significant level = 0.05 (0.05/2 = 0.025). So that tcount ttable then H1 is accepted, which means that there is a significant influence between Economic Factor variables on income, while the results of multiple linear regression tests show that Constant (Î± ) is 0.439, indicating the magnitude of the influence of Social Factors (X1), Economic Factors (X2 ), to Income (Y) meaning that if the independent variable is a constant, (X1, X2, = 0) then the income is 0.438. For the results of the coefficient of determination are Social Factors (X1), Economic Factors (X2) to the dependent variable, namely Income (Y) is 0.744. This means that 74.6% of the dependent variable, namely income, can be explained by the independent variable, namely social factors, economic factors. And the remaining 25.4% of income can be explained by other variables or other factors, here another factor is the selling price. And for the results of the F-test which shows that the Fcount is 84.568 with a sig level. of 0.000. At the level of significant value = 0.05.